Resilience in higher education students: a scoping review. Issue 6 (19th September 2019) - Brewer, Margo. L.; van Kessel, Gisela; Sanderson, Brooke; Naumann, Fiona; Lane, Murray; Reubenson, Alan; Carter, Alice
ABSTRACT: The health, wellbeing and employability of university students are key considerations within higher education. In response, interest in student resilience is on the rise. Reviews of contemporary resilience literature highlight both conceptual and methodological weaknesses, issues which hamper attempts to design effective resilience interventions. To inform the design of a student resilience program, to be piloted at three Australian universities, a scoping review of resilience specific to the higher education context was undertaken. Searches of three electronic databases (PsychINFO, CINAHL and ProQuest) were conducted. Seventy-two peer-reviewed articles published between 2007 and 2017 were included in the review. While the review reaffirms the conceptual and methodological issues found in previous resilience research, it provides a useful critique of key issues in relation to university student resilience and interventions to enhance students' resilience. Recommendations for educators and researchers are provided.